Monetary policy rule: A broad monetary conditions index for Nigeria - Baba N. Yaaba (CBN Journal of Applied Statistics, 2013)
To determine the relative importance of both the domestic and external influences on monetary policy formulation, this paper constructs a broad monetary conditions index for Nigeria. It brings together the three key channels of monetary transmission, namely interest rate, exchange rate and credit channels. The result gives dominance to exchange rate channel, followed by credit channel and interest rate channel. The resultant monetary conditions index traces fairly well the policy direction of the Central Bank of Nigeria for the studied period, hence can serve as an adequate gauge of monetary policy stance of the Bank.
Keywords: C33; E52; E58; 330; Monetary Policy; Monetary Conditions; Monetary Transmission; Cointegration